Rapid Synthesis of Dittmarite by Microwave-Assisted Hydrothermal Method - Lai zhenyu; Qian Jueshi; Lu Zhongyuan; Li Qian; Zou Qiulin (Advances in Materials Science and Engineering)
Dittmarite was obtained using MgO and (NH4)2HPO4 as raw materials via microwave-assisted hydrothermal method for 3 min at 120°C. The resulting samples were investigated by X-ray powder diffraction, scanning electron microscopy, Fourier transform infrared spectroscopy, and thermogravimetry-differential thermal analysis. The results indicate that dittmarite can be rapidly synthesized by microwave-assisted hydrothermal method. With higher temperature and longer reaction time, highly crystallized dittmarite can be obtained. Pure dittmarite can be synthesized for 3 min at 120°C, which is faster than with the use of any other reported methods.